TRAINING NEEDS IN SOCIAL ENTREPRENEURSHIP: MEASURES AND EXPERIENCE OF BULGARIA - Nelly BENCHEVA; Teodora STOEVA (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The social economy model is one of the key tools for achieving socially significant goals within the frames of a sustainable and including growth. The social entrepreneurship and social economy, as concepts, allow the creation of alternative models for conducting business. They are market-oriented and at the same time integrate all of the free market participants - employees, employers, investors, consumers and others. Social enterprises have a key role in regeneration and economic development and in the promotion of social inclusion. The aim of this article is to explore the training needs in social entrepreneurship: measures and experience of Bulgaria and skills and qualifications of business advisors to provide the necessary consulting services to social intermediaries and social enterprises. The results of a pilot study under the Erasmus+ project "Social enterprise skills for business advisors" are used. The collection of the primary data included a questionnaire survey to collect information and data by using a face-to-face interview. 104 representatives of different types of organizations from the South Central Region, administrative district of Plovdiv were interviewed.